The Effect of Service Quality on Student Satisfaction at Aisyah University of Pringsewu - Nurzanah, Eka; Marthalena, Yenny; Nugroho, Tri Adi; Wahyudi, Dian Arif; Lestari, Sastri Ayu; Soleha, Uswatun Maratu; Imelda, Vivi (Utan Kayu Publishing, 2022)
This objective of the study was to determine the effect of the quality of academic services owned by Aisyah University of Pringsewu on student satisfaction. The method used in this research is descriptive quantitative method. The types of data needed for research are primary data and secondary data. Sampling was carried out using a probability sampling method of simple random sampling, with a total of 198 respondents. The data analysis technique uses descriptive analysis and multiple regression analysis. Based on the results of the T-test there are 2 variables that have an effect, namely the Responsivenss variable (responsiveness) and Tangible variable (physical evidence), while the Reliability (reliability), Assurance (Assurance) and Emphaty (empathy) has no effect on student satisfaction. The results of this study based on the F test is the Quality of Service which consists of Reliability (reliability), Responsivenss (responsiveness), Assurane (Guarantee), Empathy (empathy) and Tangible (physical evidence) have a simultaneous and significant effect on student satisfaction. Penelitian ini bertujuan untuk mengetahui pengaruh kualitas layanan akademik yang dimiliki oleh Universitas Aisyah Pringsewu terhadap kepuasan mahasisiswa. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif deskriptif. Jenis data yang dibutuhkan untuk penelitian adalah data primer dan data sekunder. Pengambilan sampel dilakukan dengan metode probability sampling jenis simple random sampling, dengan jumlah responden sebanyak 198 responden. Teknik analisis data menggunakan analisis deskriptif dan analisis regresi berganda.Berdasarkan hasil uji T terdapat 2 variabel yang berpegaruh yakni variabel Responsivenss (daya tanggap) dan variabel Tangible (bukti fisik), sedangkan variabel Reliability (kehandalan), Assurane (Jaminan) dan Emphaty (empati) tidak berpengaruh terhadap kepuasan mahasiswa. Hasil dari penelitian ini berdasarkan uji F adalah Kualitas Pelayanan yang terdiri dari Reliability (kehandalan), Responsivenss (daya tanggap), Assurane (Jaminan) , Emphaty (empati) dan Tangible (bukti fisik) berpengaruh secara simultan dan signifikan terhadap kepuasan mahasiswa